Minimal Residual Disease Defines the Risk and Time to Biochemical Failure in Patients with Pt2 and Pt3a Prostate Cancer Treated With Radical Prostatectomy: An Observational Prospective Study - Murray, Nigel P; Aedo, Socrates; Fuentealba, Cynthia; Reyes, Eduardo; Salazar, Anibal; Lopez, Marco Antonio; Minzer, Simona; Orrego, Shenda; Guzman, Eghon (Urology Journal, 2020)
Purpose: To compare Gleason score (GS), pathological stage, minimal residual disease (MRD) and outcome after prostatectomy radical for prostate cancer. Patients and Methods: 290/357 men with GS 6 or 7 and pT2 or pT3a disease treated with radical prostatectomy participated. Blood and bone marrow were obtained one month after surgery. Circulating prostate cells (CPCs) were detected using differential gel centrifugation and immunocytochemistry with anti PSA, micro-metastasis weas detected using immunocytochemistry with anti-PSA. Biochemical failure free survival (BFFS) and restricted mean survival times (RMST) were calculated according to GS and stage. MRD was classified as negative, patients only positive for micro-metastasis and patients positive for CPCs; BFFS and RMST were calculated according to MRD sub-type. Results: GS7 (HR 3.03) and pT3a (HR 3.68) cancers were associated with a higher failure rate, shorter time to failure and associated with CPC positive MRD (p < 0.001), while G6 and pT2 with MRD negative disease (p<0.001). Men with CPC (+) MRD were at high risk of early treatment failure; 15% BFFS at 10 years, RMST 3.0 years. Men positive for only micro-metastasis were at risk of late failure, 50% BFFS at 10 years, RMST 8.0 years compared with MRD negative patients; 80% BFFS at 10 years, RMST 9.0 years. Conclusion: The sub-type of MRD identifies Gleason 6 pT2 patients with a poor prognosis and Gleason 7 pT3a patients with a good prognosis and could be used to classify men according to personal risk characteristics for the use of adjuvant treatment.